2001
DOI: 10.1074/jbc.m107986200
|View full text |Cite
|
Sign up to set email alerts
|

NADP-Glutamate Dehydrogenase Isoenzymes of Saccharomyces cerevisiae

Abstract: In the yeast Saccharomyces cerevisiae, two NADP؉ -dependent glutamate dehydrogenases (NADP-GDHs) encoded by GDH1 and GDH3 catalyze the synthesis of glutamate from ammonium and ␣-ketoglutarate. The GDH2-encoded NAD ؉ -dependent glutamate dehydrogenase degrades glutamate producing ammonium and ␣-ketoglutarate. Until very recently, it was considered that only one biosynthetic NADP-GDH was present in S. cerevisiae. This fact hindered understanding the physiological role of each isoenzyme and the mechanisms involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
79
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 140 publications
(85 citation statements)
references
References 47 publications
3
79
0
Order By: Relevance
“…The second node is directly perturbed, and it makes sense that this change results in a transcriptional response of enzymes around this node. It has indeed been shown that in a ⌬gdh1 mutant, the level of ␣-ketoglutarate is increased (19), which is consistent with a decreased expression of the genes KGD and LSC, both encoding enzymes downstream of ␣-ketoglutarate.…”
Section: Resultsmentioning
confidence: 62%
“…The second node is directly perturbed, and it makes sense that this change results in a transcriptional response of enzymes around this node. It has indeed been shown that in a ⌬gdh1 mutant, the level of ␣-ketoglutarate is increased (19), which is consistent with a decreased expression of the genes KGD and LSC, both encoding enzymes downstream of ␣-ketoglutarate.…”
Section: Resultsmentioning
confidence: 62%
“…The glutamate/ glutamine pair has been reported to play a major role in the CNM, collecting NH 3 groups from the available nitrogen sources and then serving as amine donors for the transamination of ␣-keto acids (67,68). Interestingly, during 15 N-labeled arginine assimilation, isotopic enrichment occurred earlier in glutamate than in the other proteinogenic amino acids, supporting the key contribution of this compound as a mediator for nitrogen redistribution.…”
Section: Discussionmentioning
confidence: 76%
“…Normal ploidy was recovered through the massive loss of 90% of the duplicated genes and the selective retention and further diversification of 8% of the retained paralogous copies (17). Diversification of paralogous genes whose products are involved in amino acid metabolism has led to the separation and specialization of the ancestral function of the two duplicated genes, the retention of both copies fulfilling the function carried out by the original and unique ancestral gene (10,(18)(19)(20). Subfunctionalization of paralogous pairs can be achieved through various nonexclusive molecular mechanisms, i.e., (i) modifications of the coding sequence leading to paralogous proteins with particular kinetic properties (18), (ii) modifications of the regulatory region determining the differential expression of each copy (20), or (iii) different subcellular localization (21).…”
mentioning
confidence: 99%
“…Subfunctionalization of paralogous pairs can be achieved through various nonexclusive molecular mechanisms, i.e., (i) modifications of the coding sequence leading to paralogous proteins with particular kinetic properties (18), (ii) modifications of the regulatory region determining the differential expression of each copy (20), or (iii) different subcellular localization (21). Previous work by our laboratory had suggested that an additional mechanism that could lead to functional diversification of paralogous proteins could be determined by the selective organization of homo-or hetero-oligomeric isozymes with peculiar biochemical properties (18).…”
mentioning
confidence: 99%